Simulated gastric fluid assay for estimating the digestibility of newly expressed proteins in GE crops: Missteps in development and interpretation. (November 2022) - Herman, Rod A.; Zhang, John X.Q.
Abstract: Digestive stability of a food protein in simulated gastric fluid (SGF) continues to be considered a risk factor for allergy, even though the current science does not support this belief. Methodological shortcomings of the adaption of the SGF assay for use with purified proteins has been cited as a reason to discount results that do not conform to this belief. Missteps in conducting and interpreting the results of SGF assays are reviewed here. However, these methodological shortcomings do not invalidate the conclusion that allergenic proteins are not systematically more stable to digestion than non-allergens. The growing evidence for the dual allergen exposure hypothesis, whereby sensitization to food allergens is primarily caused by dermal and inhalation exposure to food dust, and tolerization against food allergy is primarily induced by gut exposure in food, likely explains why the digestive stability of a protein is not a risk factor for allergenicity. Highlights: Digestive stability of proteins is considered a risk factor for allergenic potential. Allergens are not systematically less digestible than non-allergens. Methodological assay shortcomings have been cited to discount empirical results. However, results establish that digestibility does not correlate with allergenicity. The dual allergen exposure hypothesis suggests gut exposure favors tolerization.